Oligoclonal banding in cerebrospinal fluid assessed by electrophoresis on agarose after centrifugal sample concentration through a microconcentrator membrane. - Christenson, R; Russell, M; Gubar, K; Silverman, L; Ebers, G (1985)
We describe use of a microconcentrator membrane with a 30 000-Da cutoff for treatment of cerebrospinal fluid (CSF) specimens before detection of oligoclonal bands by electrophoresis on agarose. After centrifugation at 2000 X g for 25 min, 0.5-, 1.0-, and 2.0-mL aliquots of CSF were concentrated 15-, 25-, and 40-fold. Analytical recovery of immunoglobulins G and A from the microconcentrators was about 90% (CV 5-8%). We found good correlation between results by this method and by a silver-stain procedure in a study comparing oligoclonal banding in CSF from multiple sclerosis and control patients. After 40-fold concentration of 2 mL of CSF, 2 mg of immunoglobulin G per liter can be detected, because the analytical sensitivity of the electrophoresis is 80 mg/L.